Is Negative Emotion Differentiation Associated With Emotion Regulation Choice? Investigations at the Person and Day Level - O'Toole, Mia S.; Elkjær, Emma; Mikkelsen, Mai B. (Frontiers in Psychology, 2021)
Negative emotion differentiation (ED) has been suggested to be important for adaptive emotion regulation (ER). However, knowledge concerning how ED may impact specific ER strategy choice remains surprisingly sparse. We therefore investigated (1) if person-level negative ED was associated with habitual use of individual ER strategies, (2) how person-level negative ED was associated with daily use of individual ER strategies, and finally (3) how within-person daily fluctuations in negative ED were associated with daily use of individual ER strategies. During a 10-day experience sampling study, 90 healthy participants rated their momentary emotions and their ER efforts in response to those emotions. ER strategies included four putatively adaptive strategies (reflection, distancing, non-reactivity, reappraisal) and four putatively maladaptive strategies (rumination, experiential avoidance, expressive suppression, worry). Results revealed that negative ED at the person level was neither associated with habitual nor daily ER strategy endorsement when controlling for negative emotions. Likewise, associations between within-individual daily variation in negative ED and daily ER did not remain statistically significant after controlling for negative emotions. The results thus point to no or weak associations between negative ED and ER choice above and beyond negative emotions. Future experimental studies addressing ED at the momentary level and teasing out the ED–ER causal timeline are needed to further evaluate ED–ER associations. Findings from such research may represent an important step toward refining psychotherapeutic interventions aimed at improving emotional problems.